2012
DOI: 10.5194/bg-9-3277-2012
|View full text |Cite
|
Sign up to set email alerts
|

Regional analysis of groundwater nitrate concentrations and trends in Denmark in regard to agricultural influence

Abstract: Abstract. The act of balancing between an intensive agriculture with a high potential for nitrate pollution and a drinking water supply almost entirely based on groundwater is a challenge faced by Denmark and similar regions around the globe. Since the 1980s, regulations implemented by Danish farmers have succeeded in optimizing the N (nitrogen) management at farm level. As a result, the upward agricultural N surplus trend has been reversed, and the N surplus has reduced by 30-55 % from 1980 to 2007 depending … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
56
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 64 publications
(62 citation statements)
references
References 22 publications
6
56
0
Order By: Relevance
“…The sandy nature implies a faster drainage of water and nutrients through the soil and a better aeration that favours mineralization and slows down denitrification (Scheffer and Schachtschabel, 2002). Therefore, and in correspondence with earlier Danish studies (Kronvang et al, 2008;Hansen et al, 2012), sandy soils may be the explanation for the higher NO − 3 concentrations in the northern stream water.…”
Section: Nitratesupporting
confidence: 48%
See 1 more Smart Citation
“…The sandy nature implies a faster drainage of water and nutrients through the soil and a better aeration that favours mineralization and slows down denitrification (Scheffer and Schachtschabel, 2002). Therefore, and in correspondence with earlier Danish studies (Kronvang et al, 2008;Hansen et al, 2012), sandy soils may be the explanation for the higher NO − 3 concentrations in the northern stream water.…”
Section: Nitratesupporting
confidence: 48%
“…As pointed out in many studies (Böhlke and Denver, 1995;Ruiz et al, 2002a;Worrall and Burt, 2001), soils are able to store N, leading to poor correlations between N losses from agricultural soils and headwater quality. Consequently, N leaching is affected by past land use and management practices (Hansen et al, 2011(Hansen et al, , 2012, which varied a lot in this area during the past 300 yr (Caspersen and Fritzbøger, 2002), but a further study of this aspect was out the scope of the present study. Furthermore, the NO − 3 stored in soils can be released into sub-surface and groundwater after some time.…”
Section: Nitratementioning
confidence: 99%
“…They found that the frequency of downward nitrate trends in groundwater samples clearly increased with lower recharge age, providing proof that younger groundwater responds fastest to decreasing trends of SNB. Hansen et al (2012) further found that nitrate concentration decreased significantly more in areas with a high livestock density. Reported nitrate concentrations in Germany are higher than in the other northwestern EU member states because sampling is restricted to agricultural soils and focused on polluted regions.…”
Section: Water Qualitymentioning
confidence: 80%
“…Some of the reactive N excreted from intensive livestock systems (i.e. urine and feces) is recycled through agricultural systems in a limited way, results in N-saturation hotspots (farm soil NO 3 2 levels often reaching 300 to 400 kg N/ha per year), causing NO 3 2 contamination of groundwater Hansen et al, 2012). A major portion of the reactive N excreted from livestock systems is not recycled effectively through modern production systems as N source (WagnerRiddle et al, 2007;Centner and Newton, 2008;Schlesinger, 2009).…”
mentioning
confidence: 99%